Динаміка фотосинтетичної й азотфіксувальної активностей та продуктивність сої, інокульованої Tn5-мутантами Bradyrhizobium japonicum - Василюк, В.М.; Кірізій, Д.А.; Коць, С.Я. (Видавничий дім "Академперіодика" НАН України, 2008)
Influence of the inoculation of soybean by new Tn5-mutants of Bradyrhizobium japonicum 646 on seed productivity and change of nitrogen fixing activity (NFA) and photosynthetic rate (PR) on the different stages of plant development were studied in vegetative experiment. Two types
of dynamics of NFA and PR were shown in the symbiotic systems with different efficiencies. Tn5-mutants 21–2, 113, 35–2 and strain B. japonicum 646 belong to the first type with the maximum NFA and PR in budding with a following decrease of these indices in the phase of flowering. The second one (Tn5-mutant 17–2 and strain B. japonicum 634b) was characterized by the increase of NFA and PR during the abservation period and had the highest absolute values at flowering. We have shown the enhance of the seed yield by 16.6 and 14.3%, respectively, in comparison with wild strain B. japonicum 634b in soybean inoculated with Tn5-mutants B. japonicum 21–2 and 17–2 which had the highest NFA among the researched mutants.